2019
DOI: 10.1371/journal.pone.0226300
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of cattle with Fasciola hepatica or F. gigantica and Mycobacterium bovis: A systematic review

Abstract: The liver flukes, Fasciola hepatica and F. gigantica, are common trematode parasites of livestock. F. hepatica is known to modulate the immune response, including altering the response to co-infecting pathogens. Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a chronic disease which is difficult to control and is of both animal welfare and public health concern. Previous research has suggested that infection with liver fluke may affect the accuracy of the bTB skin test, but direction of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
0
19
1
Order By: Relevance
“…Moreover, hypersensitive skin tests like the cervical intradermal tuberculin test and comparative intradermal tuberculin are seldom practiced in the small ruminants industry due to the thinness of the skin. Furthermore, lesion detection and bacterial culture also confer poor applicability of TB detection technology in live animals ( Howell et al, 2019 ). The development of technologies for the detection of TB in live small ruminants is a big deal, and detection of lesions or tuberculous organisms at necropsy are acceptable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hypersensitive skin tests like the cervical intradermal tuberculin test and comparative intradermal tuberculin are seldom practiced in the small ruminants industry due to the thinness of the skin. Furthermore, lesion detection and bacterial culture also confer poor applicability of TB detection technology in live animals ( Howell et al, 2019 ). The development of technologies for the detection of TB in live small ruminants is a big deal, and detection of lesions or tuberculous organisms at necropsy are acceptable alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…The difference may be due to the fact that the detection of bTB lesions, in particular, depends on the diligence and thoroughness of the inspector conducting the examination [ 27 ]. Other factors that may influence the detection of tuberculous lesions in abattoirs might include underlying parasitic infections [ 28 ] and other irregularities of abattoir meat inspection [ 29 ]. Hence, cases of missed bTB lesions are a possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, co-infection with bovine viral diarrhea (BVD) virus has conflicting effects in previous studies; it is suggested to suppress the immunological response to PPD or cause rapid progression of bTB or even to have no significant effect [ 46 ]. Furthermore, co-infection with liver fluke, Fasciola hepatica and Fasciola gigantica , may affect the accuracy of bTB but the direction of the effect differs among studies [ 49 ]. It is suggested that liver fluke infection may suppress the M. bovis infection [ 46 ].…”
Section: Diagnosis Of Btbmentioning
confidence: 99%
“…It is suggested that liver fluke infection may suppress the M. bovis infection [ 46 ]. Howell et al examined the evidence to determine the effect of liver fluke infection on four outcomes relevant to bTB diagnosis: TST, IGRA, lesion detection, and bacterial culture [ 49 ]. The study supported the hypothesis that liver-fluke-infected animals are likely to have a reduced response to both TST and IGRA tests and fewer bacteria recovered/cultured from their lesions.…”
Section: Diagnosis Of Btbmentioning
confidence: 99%